Some reflections on the construction and legitimization of scientific knowledge - Horvath, Jorge Ernesto (Cadernos de Astronomia, 2025)
The practice of a scientific activity is an issue not frequently addressed and that has a large impact on the future researchers. In general, a series of postulates and beliefs are presented to the students which are far from reality, much more complex and less ideal that the discourse. We discuss these aspects in some detail, introducing the idea of a pyramidal structure of the scientific community, and point out several difficulties for a successful passage to it, dismounting in passing that ideal utopic picture.
Keywords: sociology of science; scientific knowledge; scientific practise